Schooling and beyond: essays on skill formation and learning in deprived contexts - Krutikova, S (2011)
This thesis explores learning and formation of cognitive and non-cognitive skills within formal and non-formal environments, as well as the impact of migration on fertility behaviour in three separate empirical studies. In two of the papers (Chapters 2 and 4) I utilise a 13 year individual-level panel data-set from rural Tanzania, while the third one (Chapter 3) is based on cross-sectional data that I collected in urban Bombay slums in 2007. I consider skill acquisition and learning in a number of spheres. First, I adopt the conventional notion of school-based learning and examine the role of income shocks in evolution of schooling inequalities, in rural Tanzania. I find evidence of shock-induced permanent changes in the schooling of those affected by the shocks in later childhood (age 7-13), 10-13 years later. Further, I find suggestive evidence that the household short-term labour response may to be one of the mechanisms for these long-term effects. Next, I broaden the definition of learning to include acquisition of non-cognitive skills. Although there is growing recognition of the importance of these, there is no evidence, within a developing country context, on effectiveness of interventions targeting them. The second paper is an evaluation of a long-term non-formal schooling intervention in Bombay slums, which works on raising non-cognitive skills, including self-esteem, a sense of agency, and aspirations of children. It shows that, like cognitive skills, non-cognitive skills can be effectively raised through sustained intervention, offering evidence of substantial positive programme effects. The final paper turns to examining the impact of migration among young women on fertility behaviour. Econometric panel data methods are combined with an instrumenting strategy to offer evidence of a causal positive impact of migration on the age at which women start having children, which is shown to be likely to have permanent effects on total fertility. The findings are most consistent with the presence of temporary post migration disruption effects.